Pemberdayaan Masyarakat Melalui Chemistry Enterpreneurship di Desa Gondang Kabupaten Lombok Utara - Ratna Azizah Mashami; Menik Aryani; Ahmadi Ahmadi (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2019)
Gondang Village is one of the villages that was badly damaged by the earthquake a year ago. In addition to swallowing fatalities, the earthquake also resulted in badly damaged houses and public facilities. Employers lose their business, so too workers lose their jobs. To start a new business, the victims did not have the capital and did not know what kind of business they would pursue. This service aims to provide skills to the community through chemistry entrepreneurship so that people can start entrepreneurship. Chemistry entrepreneurship involves the process of converting innovations from chemicals into products that can be marketed for commercial gain. The products to be made this time are a liquid detergent, dish soap, softener, and sof trika. These four products are basic needs in the household so this business opportunity is very promising. The KKN PPM program was held for 1 month. There were 93 people involved in this activity representing 11 hamlets. The stages of the KKN PPM activities are preparation, trial, production, and marketing review. All of these activities involved 20 students who worked with the community. The people of Gondang Village have received training in making liquid detergent, dish soap, softener, and hydrophobic along with a sales strategy. Product sales have increased in number based on the first and second evaluations. Community income also increased. The resulting product has been officially launched as a superior product in Gondang Village. The service team and students have successfully carried out community empowerment through chemistry entrepreneurship.